Love her wild : poems (Atria Paperback, 2017)
"The first collection of poetry by Instagram sensation Atticus. Love Her Wild is a collection of new and beloved poems from Atticus, the young writer who has captured the hearts and minds of hundreds of thousands of avid followers on his Instagram account @atticuspoetry, including superstars like Karlie Kloss and Shay Mitchell. He was dubbed the "#1 poet to follow" by Teen Vogue and "the world's most tattoo-able" poet by Galore magazine, in Love Her Wild, Atticus captures what is both raw and relatable about the smallest and the grandest moments in life: the first glimpse of a new love in Paris; skinny dipping on a summer's night; the irrepressible exuberance of the female spirit; or drinking whiskey in the desert watching the rising sun. With honesty, poignancy, and romantic flair, Atticus distills the most exhilarating highs and the heartbreaking lows of life and love into a few perfectly evocative lines, ensuring that his words will become etched in your mind--and will awaken your sense of adventure"--